Bio‐Inspired Band‐Gap Tunable Elastic Optical Multilayer Fibers. (27th January 2013) - Kolle, Mathias; Lethbridge, Alfred; Kreysing, Moritz; Baumberg, Jeremy J.; Aizenberg, Joanna; Vukusic, Peter
<x xml:space="preserve">Abstract</x> The concentrically‐layered photonic structure found in the tropical fruit Margaritaria nobilis serves as inspiration for photonic fibers with mechanically tunable band‐gap. The fibers show the spectral filtering capabilities of a planar Bragg stack while the microscopic curvature decreases the strong directional chromaticity associated with flat multilayers. Elongation of the elastic fibers results in a shift of the reflection of over 200 nm. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>